Bibliometric Mapping of Character Values Education in Schools - Hafid, Abdul; Sudarmin, Sudarmin; Salmia, Salmia (Yayasan Keluarga Guru Mandiri, 2025)
This research is motivated by the critical need for an in-depth understanding of research trends concerning character education values within a global context, specifically those indexed in Scopus. The objective is to map and analyze these research trends from 2013 to 2023. The methodology employed is a bibliometric review, with data extracted from Scopus in November 2022 using the keyword